Importance of physiotherapy in sequelae of post-Covid-19 patients: Importancia de la fisioterapia en secuelas de pacientes post Covid-19 - Salazar Trujillo, Juan Pablo (2024)
Dear Editor,   As nursing students, we have read with great interest the article titled "Functionality before and after physiotherapy in post-COVID-19 patients" (1), published in volume 23, issue 3 (2023) of the Revista de la Facultad de Medicina Humana. This study highlights the importance of functional physical therapy in patients with post-COVID-19 sequelae. We consider it relevant to express our concern regarding the increase in these sequelae in our country, which aligns with the findings of Goicochea et al. (2), who report that 28.8% of post-COVID patients experienced sequelae, predominantly respiratory, musculoskeletal, and neurological, as shown in Table 1. This increase may be related to the large percentage of unvaccinated individuals. The objective of that article was to highlight the physical and respiratory functional effects in post-COVID-19 patients, with the goal of improving and alleviating the symptoms associated with this condition.